O líder em Exame: o enquadramento da liderança na mídia de negócios - Schaefer, Ricardo (2014)
A vast and growing literature on studies of framing has emerged in the last decades and the concept has gained prominence in the field of communication. Recent analyses, however, have pointed out two principal criticisms that these studies have been receiving: a certain vagueness or a conceptual multiplicity and the lack of a systematic methodology between the research. This work has search to contribute on the solution of this problem by doing a historical research on framing and bringing together the different advances that investigations regarding both the theoretical aspect as its empirical application have brought. To achieve this scope, besides the literature review and analysis of the evolution of research, this study has applied a proposal of operationalization of the concept on an empirical case, analysing the changes in the journalistic framing on scripts about leadership published in Exame magazine between 1970 and 2012. Adapting the methodology of framing indirect analysis for the business media, this research has investigated how the framing of leadership has changed along the 42 years of the magazine. 92 articles were analyzed, selected on 7 years of publication, identifying six frames of the leader: founding entrepreneurs, career executive, successors heirs, home silverware, beginners entrepreneurs and leaders of the second level. The research has also found changes in the prevalence of these frames by new editorial strategies adopted over the years by the publication. One can also conclude that in the analysed articles, the figure of the leader plays a central role, being presented as the main responsible by the course of corporate events. Presenting the leader, inserted in an organizational theme, Exame magazine describes its actuation mode and how the context in which he is inserted influences the way of conduction of their team. The publication also presents, through different symbolic devices, personality traits and characteristics of the leader, their behavioural styles, contingency and situational factors that influence its action, and how the leader also happens to be an agent and a promoter of values and meanings in business contexts.